USE OF MEDIA MAKE A MATCH ON CHANGES IN KNOWLEDGE ABOUT CARIES (STUDENTS OF WACHID HASJIM 2 CLASS PRIMARY SCHOOL SURABAYA): PENGGUNAAN MEDIA MAKE A MATCH TERHADAP PERUBAHAN PENGETAHUAN TENTANG KARIES (SISWA SD WACHID HASJIM 2 KELAS ATAS SURABAYA) - Vania Pramestya (Poltekkes Kemenkes Surabaya, 2025)
Dental caries is a major health problem that attacks the younger generation. Tissue damage that starts from the surface of the tooth, continues to the enamel and dentin, until finally reaching the pulp is a characteristic of dental caries. Problem statement: It is still not possible to achieve a caries-free rate of 50%. upper class at SD Wachid Hasjim 2 Surabaya. Academic caries affects 82% of students. The purpose of the survey was to find out how much students at Wachid Hasjim 2 Elementary School Surabaya understand about dental caries. Technique: Pretest and Posttest research designs are used in this type of quasi-experimental research. The population in this study was upper class students at SD Wachid Hasjim 2 Surabaya (93 students). The analysis techniques used are ANOVA and Post Hoc Multiple Comparisons. Results: There is a difference in knowledge before and after counseling using Make A Match media to upper class students at SD Wachid Hasjim 2 Surabaya. Pretest: class 4 mean±SD.Deviation (56.71±10.747), class 5 mean±SD.Deviation (48.80±10.029), class 6 mean ±SD.Deviation (58.05±7.198) and Posttest: class 4 mean ± SD.Deviation (82.34±6.718), class 5 mean ± SD.Deviation (77.80±5.605), class 6 mean ± SD.Deviation (80.69±7.382). With a pretest significance value of 0.002 and posttest 0.013 (ρ <0.050). There is a real difference. Conclusion: There is an increase in knowledge about caries after counseling using Make A Match media to upper class students at SD Wachid Hasjim 2 Surabaya.